Затраты энергии на дыхание, рост и размножение у Artemia salina (L.) - (:unkn) unknown (Biologiya morya, 1968)
The size-weight relations, caloric value, fat content, number of eggs produced, respiration and growth of Artemia salina were determined. According to the data obtained the total energy budget for Artemia has been calculated for different periods and for the whole life-time equal to 130 days. The energy of the food assimilated during the whole life is 60 calories per animal, and 120 cal of consumed food. A shrimp consumes during this time 24 mg of dry weight of food, the latter amounts to 5 cal/mg. The daily ration during the reproduction period was found to be 0.2 mg of dry weight of food per specimen, that gives about 40% of dry body weight of Artemia. The growth coefficient of the first order (K1) and the second order (K2) were determined. The first is referred to as the gross efficiency and the second — as the net efficiency of growth. The received data show that the both coefficients of the pre- reproduction and reproduc-tion period of life are different (K1=12.5% and 0.6%; K2=28.1% and 1.8% respectively). However, such decrease in the coefficients is observed when we take into account only the increase energy of the body weight growth disregarding the other elements of the plastic metabolism. Otherwise these coefficients will not change and their values during the pre-reproduction and reproduction periods are similar (K1=17.8% and 17.9%, K2=35.6% and 35.8% respectively). The total energy of growth and energy of respiration are almost equal. The ecological efficiency of Artemia population constitutes 18%.
The expenditure of energy on respiration, growth and reproduction in Artemia salina (L.)